Pattern of Injury among Orthopaedic Inpatients in a Teaching Hospital in Central Nepal - Bidary, Suraj; Pandey, Suresh; Gupta, Hemant Kumar; Aryal, Roshani; Bhattarai, Kushal (Journal of College of Medical Sciences-Nepal, 2020)
Introduction: Injury is a major cause of morbidity and mortality globally with the majority of them being orthopaedic in nature and are the resultants of fall, road traffic accidents (RTA), physical assault amongst others. The aim of this study was to determine the patterns of musculoskeletal injury among orthopaedic inpatients in a tertiary care teaching hospital in Nepal. Methods: It was a cross-sectional study conducted in the department of orthopaedic surgery at College of Medical Sciences and Teaching Hospital (COMS-TH), Bharatpur from January to December 2019. Patients presenting with orthopaedic injury and admitted and treated as inpatients were assessed for their demographic details, mode of injury and other patterns of injury and descriptive analysis was done. Results: In a total of 1027 patients, the mean age was 33.4 years (range: 1.0 - 95.0). Most of them (74.5%) were male. Right side was the most predominant side of injury (53.8%). Students were most commonly affected groups (34.8%). RTA was the most common mode of injury (66.9%). The commonest pattern of injury was fracture (70.1%). Closed bony injuries were sustained by 74.1%. Head injury was the most commonly associated injury. Conclusions: The commonest mode of injury was RTA. Closed fracture was the most common type of fracture. Extremity injury was the most common site and head injury was the commonest associated injury. These patterns can serve as valuable tools in clinical decision making and further research studies.